Synthesis, Characterization and Photocatalytic Activity of Fe3+ Doped Mesoporous TiO2 Prepared by a Modified Sol-Gel Process - Hu, S.Z.; Li, F.Y.; Fan, Z.P. (Asian Journal of Chemistry, 2012)
Fe3+ doped mesoporous TiO2 was prepared by a modified sol-gel process. The obtained samples were characterized by X-ray diffraction, N2 adsorption, FT-IR, UV-VIS spectroscopy and XPS analysis. The prepared TiO2 samples were around 10-15 nm in size with narrow particle size distribution. The Ti-O-Si bond formed between TiO2 and MCM-41 fixed the TiO2 on the MCM-41 surface which restricted the agglomeration and growth of the TiO2 particles. The performance in photocatalytic degradation of methylene blue under visible light indicated that the addition of MCM-41 greatly improved the photocatalytic activity of prepared TiO2 catalysts. The doping content of Fe3+ and calcination temperature significantly influenced the photocatalytic activity of TiO2 catalysts.